Computer-assisted fabrication of a cutting guide for marginal mandibulectomy and a patient-specific mandibular reconstruction plate: A case report. Issue 5 (September 2021) - Dong, Quang Ngoc; Karino, Masaaki; Osako, Rie; Ishizuka, Shinji; Toda, Erina; Kanayama, Junichi; Sato, Sho; Okuma, Satoe; Okui, Tatsuo; Kanno, Takahiro
Abstract: Marginal mandibulectomy is the treatment of choice when seeking to preserve mandibular continuity. In some cases, the remaining height of the mandibular body is inadequate to sustain the functional load; mandibular reinforcement with a reconstructive plate is necessary. Treatment planning prior to marginal mandibulectomy is sometimes challenging for the novice surgeon; the risk of complications, including iatrogenic fracture, is high. Additionally, intra- or pre-operative bending of the reconstructive plate on a three-dimensional (3D) model is associated with an unavoidable risk of inaccuracy. Recently, virtual planning using surgical guides and patient-specific implants has become popular. Using image manipulation and 3D design software, the surgeon can now precisely translate the preoperative plan to the operation theater. The reconstruction plate meets the patient's needs and the surgeon's desires. Although some limitations remain, surgeons can now work more accurately and efficiently. The patient described in the present report had recurrent ameloblastoma of the right mandibular body; marginal resection and reinforcement with a reconstruction plate were required. We present the workflow from virtual surgical planning to actual surgery. Postoperative computed tomography findings reflected concordance between the treatment plan and the surgical results.